Morfologia das glândulas salivares maiores de preás (galea spixii wagler, 1831) - Rebouças, Carlos Eduardo Vale (Universidade Federal Rural do Semi-Árido, 2018)
Morphophysiology studies with wild animals are pertinent, since they provide data that serve as a basis for the adoption of attitudes towards the creation of plans for zootechnical, sanitary and alimentary management, allowing the preservation and maintenance of these species raised in captivity. Studies about the morphology of preás approach the various systems, but not a single study makes reference to both topography and structure arrangement of their salivary glands. This research had the objectives of describing the morphology of the salivary glands of the Galea spixii, based on macroscopic techniques, conventional light microscopy, electronic transmission microscopy, electronic scanning microscopy and histochemistry. The protocols were authorized by the ICMBio and the Ethics Committee on the Use of Animals, for 12 adult animals. The animals were dissected and the glands were photodocumented and macroscopically characterized. Then, fragments from each gland were collected and processed according to Hematoxylin-Eosin, Schif Periodic Acid, Gomori Trichome and Alcian Blue staining techniques. 5-micrometer sections were stained, analyzed and photographed under a Leica RM2125 RT® microscope. The results allow us to state that the Spix’s yellow-toothed cavy has four pairs of major salivary glands represented by the parotid, mandibular, zygomatic and sublingual glands. They are lobulated, constituted by mucous and serous acini, they secrete mucins of acid of a neutral nature and commonly present intercalated, striated and excretory ducts. The ultrastructure of the acinar cells suggests that they have great cellular and confirm what was establistshed basead at light microscopy. Among the glands, only the mandibular glands are lobed and also contain granular ducts
Keywords: Macroscopia; Histoquímica; Galea spixii; Ácinos; Ductos; Macroscopy; Histochemistry; Galea spixii; Acini; Ducts; CIENCIAS AGRARIAS::MEDICINA VETERINARIA